EVALUASI KEBERADAAN WEB GIS PADA SITUS WEB RESMI PEMERINTAH KABUPATEN/KOTA DAN PROVINSI - , ERNA KUSUMAWATI, Heri Sutanta, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The advancement of internet technology is one factor triggering the beginning of egovernment policy in Indonesia. Government institutions were asked to have official website. Some official websites of district/city and provincial government in Indonesia have showed spatial information, such as map and webGIS. This research aims to identify spatial data dissemination through webGIS on the district/city and provincial government official website. The data were collected between March and April 2013 by a survey on webGIS in the official website of district/city and provincial government. The survey covered websites of 497 distrcit/city and 33 provinces. Passive method is used in this research, in which the researcher evaluate the websites without any correspondence. The following parameters were used to evaluate the webGIS:webpage address, institution of the webGIS provider, base map, user interface ability, and the webGIS platform. The survey found that there are 16 district/city and 4 province that have webGIS in their official website. However, are some webGIS were located in un-official governmentâs website domain (*.go.id). Government institutions who provide include Bappeda, Public Work and Agricultural Agency.. The platform for the webGIS are map server, java runtime, SVG, GML, Gmap API, and Flash player. User interface interaction was evaluated according to the navigation toolbars in web GIS page. There are some kinds of base map in web GIS page. They are administration map, land use map, google map, and images. The findings show that the use and ownership of webGIS on the local government websites can be considered very low, with relatively simple features. Key words : assessment, web GIS, government, district, city, province